Pengaruh Edukasi Kesehatan tentang Bahaya Game Online terhadap Pengetahuan dan Sikap Remaja - Wahyuningsih, Sri; Andayani, Sri Astutik; Munir, Zainal (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Online games are internet-based games that allow multiple players to play simultaneously through online networks. These games have a strong appeal that often makes adolescents more interested in playing than studying, while also carrying the risk of addiction. This study aimed to analyze the effect of health education about the dangers of online games on adolescents’ knowledge and attitudes. The research applied a Quasi-Experimental design with a pretest-posttest control group. The sampling technique was total sampling involving 50 respondents, consisting of 25 in the intervention group and 25 in the control group. Data were analyzed using a Paired T-Test. The results revealed a significant difference in the intervention group (p=0.001 < 0.05) after receiving education, while no difference was observed in the control group. It can be concluded that health education using audiovisual media is effective in improving adolescents’ knowledge and attitudes regarding the dangers of online games.